Global Protestant missions politics, reform, and communication, 1730s-1930s - Gibbs, Jenna M. 1961- (Studies in world Christianity and interreligious relations, 2020)
The book investigates facets of global Protestantism through Anglican, Quaker, Episcopalian, Moravian, Lutheran Pietist, and Pentecostal missions to enslaved and indigenous peoples and political reform endeavours in a global purview that spans the 1730s to the 1930s. The book uses key examples to trace both the local and the global impacts of this multi-denominational Christian movement. The essays in this volume explore three of the critical ways in which Protestant communities were established and became part of a worldwide network: the founding of far-flung missions in which Western missionaries worked alongside enslaved and indigenous converts; the interface between Protestant outreach and political reform endeavours such as abolitionism; and the establishment of a global epistolary through print communication networks. Demonstrating how Protestantism came to be both global and ecumenical, this book will be a key resource for scholars of religious history, religion and politics, and missiology as well as those interested in issues of postcolonialism and imperialism